Menggali Potensi Kampung melalui Pemetaan Partisipatif: Pendekatan Komunitas dalam Pembangunan Berkelanjutan di Dupak Magersari Surabaya - Erina Miroslove, Diva Tifany; Umamah, Rosifatul; Falasifah, Nihlatul (Al-I'timad: Jurnal Dakwah dan Pengembangan Masyarakat Islam, 2024)
Sustainable development is a timeless topic. Behind it are a myriad of aspirations for current and future generations, both from the economic, social and environmental aspects. The concept that is promoted is development that promotes the fulfillment of the needs of the present without involving the ability of the next generation to achieve 17 goals, which are often referred to as sustainable development goals (SDGs) or Sustainable Development Goals (SDGs). One of them is sustainable cities and communities. This should be realized in the village of Dupak Magersari RT 01 which is the study in this research. Researchers tried to explain the potential through participatory mapping by emphasizing the active involvement of many people such as communities and even stakeholders. The goal is to hold the community in maintaining and developing their village in a sustainable manner. The analysis is based on the Participatory Rural Appraisal (PRA) approach, which is a technique to stimulate community participation in various activities, starting from the social analysis stage, planning, implementation, evaluation to program expansion. The result is an alignment between the concept of sustainable development and the mapping practices studied. The community can make sustainable planning through the findings of five basic capitals, including natural, human, financial, physical and social capital.